2020
DOI: 10.1016/j.rbmo.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation during the COVID-19 pandemic: mitigating the viral contamination risk to reproductive cells in cryostorage

Abstract: Reopening fertility care services across the world in the midst of a pandemic brings with it numerous concerns that need immediate addressal, such as the impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) on the male and female reproductive cells and the plausible risk of cross-contamination and transmission. There exists little literature on confirmatory reports of the association of SARS-CoV-2 with reproductive tissues, gametes, and embryos due to the novelty of the disease. Cryobanking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…To employ these strategies for COVID-19 patients, extra precautionary measures should be undertaken during the handling of semen to reduce the chances of viral transmission [ 85 ]. Some of the measures for the elimination of the risk of cross-contamination and transmission through cryobanking services include testing both partners for SARS-CoV-2 before initiating treatment, use of closed-carrier cryodevices and sanitary cryostorage protocols [ 86 ]. Some embryologists have advocated placing all new cryopreserved specimens into a quarantine tank until patients are determined to have negative viral test results at some future time, especially when dealing with donor semen.…”
Section: Sars-cov-2 and Male Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To employ these strategies for COVID-19 patients, extra precautionary measures should be undertaken during the handling of semen to reduce the chances of viral transmission [ 85 ]. Some of the measures for the elimination of the risk of cross-contamination and transmission through cryobanking services include testing both partners for SARS-CoV-2 before initiating treatment, use of closed-carrier cryodevices and sanitary cryostorage protocols [ 86 ]. Some embryologists have advocated placing all new cryopreserved specimens into a quarantine tank until patients are determined to have negative viral test results at some future time, especially when dealing with donor semen.…”
Section: Sars-cov-2 and Male Fertilitymentioning
confidence: 99%
“…Some embryologists have advocated placing all new cryopreserved specimens into a quarantine tank until patients are determined to have negative viral test results at some future time, especially when dealing with donor semen. Furthermore, all gametes and embryos should go through extensive washing to dilute out potential viral contamination to reduce the possibility of contamination with SARS-CoV-2 [ 86 , 87 ]. The use of high-security straws may also minimize the risks associated with cryopreserving sperm during the pandemic.…”
Section: Sars-cov-2 and Male Fertilitymentioning
confidence: 99%
“…However, it may be important to perform a Covid screening during fertility treatment, for which there are already guidelines for conduct for fertility care, identified and summarized in the study of Papathanasiou (34) For patients who are interested in sperm cryopreservation, some rules should be followed. Adiga SK (35) illustrated that the measures aimed at minimizing the risk of viral contamination in sperm cryopreservation are: blood tests before starting treatment, fully follow the correct protocols of cryopreservation and proper washing of gametes and embryos during preservation with sterile LN2. Although in some studies the virus has been identified in the testes and there is significant evidence of hypogonadism and hypotestosteronemia, further data is needed to better understand the effects of this virus on reproductive organs, to identify how the virus eventually affects fertility parameters and to ensure that the testis is not a virus reservoir (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Adiga and colleagues reviewed the question of how to mitigate viral contamination risk, with reference to the cryopreservation of reproductive cells. They concluded that cryostorage using LN 2 may involve the risk of cross-contamination by viral pathogens, suggesting the adoption of strategies to prevent the possible impact of the COVID-19 pandemic [ 20 ]. Further caution is suggested by the study of Lee et al They observed that 1–5 μm aerosol mist particles form 10–20 cm above the LN 2 –air interface, probably due to condensation, evaporation, and floating of particles.…”
mentioning
confidence: 99%